2013
DOI: 10.1590/s1806-83242013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Caries risk assessment in chilean adolescents and adults and its association with caries experience

Abstract: Cariogram is a computer program that uses an algorithm to assess caries risk. Although the use of Cariogram has recently increased, little information is available regarding its effectiveness in adults. This study aimed to determine whether caries risk from Cariogram relates to caries experience in adults. One hundred and eighty Cariogram files were completed from patients aged ten to fifty-six years (mean: 23.28 years). Seven factors from the software were included from patient records to complete the Cariogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
2
13
0
2
Order By: Relevance
“…software has been developed and validated to illustrate graphically the chance of an individual avoiding caries in the near future. 9,10,11,12 Cariogram has been used to predict caries in children, 12 adults 13,14,15,16,17,18,19 and the elderly, 20 and the scientific evidence regarding its prediction efficiency is still questionable. For adults, despite some studies reporting a high predictive value for Cariogram risk levels, 13,18 other studies have not found a correlation between caries experience and any single risk factor proposed by Cariogram.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…software has been developed and validated to illustrate graphically the chance of an individual avoiding caries in the near future. 9,10,11,12 Cariogram has been used to predict caries in children, 12 adults 13,14,15,16,17,18,19 and the elderly, 20 and the scientific evidence regarding its prediction efficiency is still questionable. For adults, despite some studies reporting a high predictive value for Cariogram risk levels, 13,18 other studies have not found a correlation between caries experience and any single risk factor proposed by Cariogram.…”
Section: Introductionmentioning
confidence: 99%
“…For adults, despite some studies reporting a high predictive value for Cariogram risk levels, 13,18 other studies have not found a correlation between caries experience and any single risk factor proposed by Cariogram. 17,19 The use of Cariogram in an adult population might be useful to try to modify caries-related behaviors and increase patients' motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical characteristics are stronger predictors than nonclinical ones, 18,20 evidence suggests that behavioural and other nonclinical risk factors also allow CRA, without the need for a clinical examination performed by a skilled person. 21 The proposed tool contains those behavioural risk or protective factors, the presence or absence of which could be assessed by the child care providers by interviewing the mother, without the need for an oral examination. Oral examination of every child was conducted on the same day at the school by the principal investigator, who was blind to the results of the questionnaire responses.…”
Section: Introductionmentioning
confidence: 99%
“…El riesgo cariogénico, definido como la probabilidad de incidencia de caries en un período de tiempo determinado, que implica además los cambios en el tamaño y/o actividad de lesiones ya presentes, es fundamental para la toma de decisiones, manejo clínico y planificación (Ministerio de Salud, 2009). Cuenta con variados instrumentos para su medición, pero ninguno es confiable, ni tampoco son comparables entre sí (Hänsel Petersson et al, 2002;Gómez, 2008;Giacaman et al, 2013). Por lo tanto, los instrumentos y los estudios existentes representan un problema al momento de servir como base para aventurar conclusiones y para la creación de políticas públicas de salud.…”
Section: Introductionunclassified